Geometric communication in organizations. A review from the administrative sciences - Arcia-Hernández, Pedro; Zúñiga, Juan Manuel Martínez; Pruneda-Ávila, Nancy Elizabeth; Espíritu-Martínez, Antony Paul; Yepes, Isabel Cristina; Rincón-Moreno, Mauricio; Ibarra-Sandoval, Fredy; Casanueva-Yánez, Galvarino (Journal of Ecohumanism, 2025)
The aim of this paper is to interpret geometric communication in business organizations from the perspective of administrative sciences. Among the main findings, it stands out that geometric communication within modern educational organizations is a complex whole that links institutional purposes and individual interests, giving a nuance to the information that is communicated not only by the personality of the informants, but also by the objects and people that surround them. without neglecting feelings, emotions and moods. To this end, geometric communication is understood as a process where self-regulation must be included as a dimension that articulates all the others (contour, environment and surroundings). Likewise, it is concluded that geometric communication is a guarantor of the good management of the educational leader, since it articulates the elements of authority and power, with those of interpersonal relationships and affectivity.